2022
DOI: 10.1186/s40001-022-00923-5
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 and LAG-3-positive T cells are associated with clinical outcomes of relapsed/refractory multiple myeloma patients

Abstract: Objective To investigate the frequency of PD-1 and LAG-3-positive T cells in relapsed/refractory multiple myeloma (RRMM) patients and its clinical significance. Methods This prospective observational study enrolled a total of 71 RRMM patients, as well as 70 MM patients (non-refractory) and 70 healthy individuals during January 2018 to March 2021. The frequency of circulating CD4+ and CD8+ T cells expressing PD-1 and LAG-3 was analyzed using flow cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…LAG-3 has been shown to be an important immune checkpoint in the pathogenesis and progression of myeloma. PD-1/LAG-3+ T cells are significantly enriched in patients with RRMM compared to NDMM ( 98 , 99 ). Targeting the LAG-3/GAL-3 pathway has been shown to result in proliferation of MM specific T cells in combination with immunotherapy ( 100 ).…”
Section: Immune Checkpoint Blockade In Multiple Myelomamentioning
confidence: 99%
“…LAG-3 has been shown to be an important immune checkpoint in the pathogenesis and progression of myeloma. PD-1/LAG-3+ T cells are significantly enriched in patients with RRMM compared to NDMM ( 98 , 99 ). Targeting the LAG-3/GAL-3 pathway has been shown to result in proliferation of MM specific T cells in combination with immunotherapy ( 100 ).…”
Section: Immune Checkpoint Blockade In Multiple Myelomamentioning
confidence: 99%
“…Furthermore, Alissa Visram et al reported that marked downregulation of interferon, TGF-β, IL-6, and TNF-α signaling pathways in abnormal plasma cells from patients with triple-refractory multiple myeloma (TRMM) compared to newly diagnosed or relapsed cases, indicating lower responsiveness of TRMM to new immunotherapies [36,37]. Ming Chen et al reported that the frequency of CD4 + PD-1+, CD8 + PD-1+/LAG-3+, as well as IL-6, IL-17, and TNF-α were found as risk factors for the incidence of relapsed/refractory MM (RRMM) in all MM [38]. Particularly, IL-6 and TGF-β not only influence the treatment outcomes but also the prognosis of MM.…”
Section: The Immune and Metabolic Microenvironment In MMmentioning
confidence: 99%
“…A currently available prospective study enrolled 71 patients with RRMM, 70 patients with MM, and 70 healthy controls. By measuring CD6 and CD17, as well as cytokines including IL-4, IL-8, TNF-α, and TGF-β, the clinical severity of patients with RRMM was found to be strongly correlated with the frequency of PD-1 and LAG-3 positive T cells, which also implies that LAG-3 and PD-1 are potential biomarkers for the diagnosis of RRMM, directly affecting the prognosis and clinical outcome of patients [ 64 ]. A phase I/II randomized trial in 2019 in patients with relapsed refractory multiple myeloma is designed to evaluate two agents, anti-LAG-3 and anti-TIGIT, for their immune effects and safety as single agents and in combination with pomalidomide and dexamethasone.…”
Section: Mechanisms Of Immune Checkpoint In Multiple Myelomamentioning
confidence: 99%